THE OPTIMAL FLOW IN DYNAMIC NETWORKSWITH NONLINEAR COST FUNCTIONS ON EDGES - Fonoberova, Maria; Lozovanu, Dmitrii (Institutul de Matematică şi Informatică al AŞM, 2004)
In this paper we study the dynamic version of the nonlinear minimum- cost flow problem on networks. We consider the problem on dynamic networks with nonlinear cost functions on edges that depend on time and flow. Moreover, we assume that the demand function and capacities of edges also depend on time. To solve the problem we propose an algorithm, which is based on reducing the dynamic problem to the classical minimum-cost problem on a time-expanded network. We also study some generalization of the proposed problem.
Keywords: dynamic networks; network flow; flows over time; minimum cost flows